A case study on Malaysia and Singapore: Nexus amongst competitiveness, cost of living, wages, purchasing power and liveability. Issue 2 (19th March 2018) - Tan, Khee Giap; Chuah, Hui Yin; Luu, Nguyen Trieu Duong
Abstract : Purpose: Malaysia and Singapore had parted more than five decades ago. Much of the existing literature concerned about the bilateral ties between two economies focusing on the political economy perspective. This paper aims to provide insights on the economic development and prospects of Malaysia and Singapore at the national level. In addition, this paper also makes a pioneering attempt at conducting a comprehensive comparative analysis between Malaysia and Singapore at the city level. Design/methodology/approach: This paper offers a case study of Malaysia and Singapore by assessing their national economic competitiveness, urban standards of living and quality of life. The paper leverages on a series of indices such as the competitiveness index for ASEAN-10, the cost of living, wages and purchasing power of ordinary residents, as well as the liveable cities index to perform the analysis. Findings: In terms of national competitiveness, the analysis shows that Singapore and Malaysia have been leading the ASEAN region from 2000 onwards, being the top- and second-ranked, respectively. Malaysia still lags Singapore in several aspects such as attractiveness to foreign investors and standard of living, education and social stability despite insignificant differences in the ranking. City-level analysis shows that the cost of living in Singapore is almost double of that in Kuala Lumpur, although living in Singapore is more affordable owing to the higher wage rate received by the ordinary citizens. Originality/value: This paper contributes to the literature in several ways. First, this paper assesses economic development in Singapore and Malaysia instead of focusing on cross-straits relations. Second, the study reflects the view that the improvement of standards of living and quality of life for ordinary residents is paramount to economic development. The competitiveness index and city-level benchmarks used in the paper reflect the standards of living and the quality-of-life dimensions. Third, the focus on city-level analysis in addition to conventional national-level analysis helps to provide policymakers with practical policy implications against the backdrop of rapid urbanisation.